Research on relay related handover security in LTE-A - Hao WU; Tao WANG; Shao-bo WU (Tongxin xuebao)
As one of the key technologies in LTE-A, relay can both optimize coverage of the network and increase the system capacity. However, the introducing of relay also brings many security challenges to the system. The security is-sues in relay related handover processes were mainly analyzed, and then the corresponding solutions were proposed for security handling. With those solutions, mobile users in the network can communicate effectively after the handover proc-ess. The designed process was also analyzed by using Petri network model. Finally, the handover security of mobile relay was discussed.